Relationship between OCT-derived plaque characteristics, CTA-derived coronary inflammation, and CMR-derived global coronary flow reserve in patients with acute coronary syndrome. (3rd October 2022) - Sugiyama, T; Kanaji, Y; Hoshino, M; Hada, M; Misawa, T; Nagamine, T; Ueno, H; Matsuda, K; Sayama, K; Yonetsu, T; Sasano, T; Kakuta, T
Abstract: Background: The presence of layered plaque is suggestive of recurrent thrombotic events. However, the impact of layered plaque detected by optical coherence tomography (OCT) on coronary inflammation and coronary flow reserve remains unclear. Purpose: We aimed to investigate the association of OCT-derived layered plaque with pericoronary adipose tissue inflammation assessed by coronary computed tomography angiography (cCTA) and global coronary flow reserve (G-CFR) assessed by cardiac magnetic resonance imaging (CMR) in patients with acute coronary syndrome (ACS). Methods: We investigated 88 patients with first ACS who underwent preprocedural cCTA and OCT imaging of the culprit lesion, and CMR after percutaneous coronary intervention (PCI). All patients were divided into four groups according to the OCT-derived culprit plaque characteristics: layered vs. non-layered plaque; and plaque rupture vs. plaque erosion. Coronary inflammation was assessed by the mean value of pericoronary adipose tissue (PCAT) attenuation (−190 to −30 HU) of the three major coronary vessels. G-CFR was obtained by quantifying absolute coronary sinus flow at rest and during maximum hyperemia. CCTA and CMR findings were compared between the groups. Results: In a total of 88 patients, layered plaque [L] with plaque rupture [PR] was observed in 25 patients, layered plaque with plaque erosion [PE] was observed in 26 patients, non-layered plaque [NL] with PR was observed in 23 patients, and non-layered plaque with PE was observed in 14 patients, respectively. Three-vessel-PCAT attenuation value (L-PR vs. L-PE vs. NL-PR vs. NL-PE; −68.13±6.18 vs. −69.01±6.72 vs. −69.76±4.04 vs. −74.61±5.63 HU, P=0.009) and culprit vessel PCAT attenuation value (L-PR vs. L-PE vs. NL-PR vs. NL-PE; −66.39±7.38 vs. −68.94±8.06 vs. −70.01±5.76 vs. −75.45±6.60 HU, P=0.003) showed the graded difference between the four groups. G-CFR value also showed the graded difference between the four groups (L-PR vs. L-PE vs. NL-PR vs. NL-PE; 2.26 [1.80–2.87] vs. 2.24 [1.72–3.13] vs. 2.97 [2.24–3.83] vs. 3.18 [2.67–4.08], P=0.022). Conclusions: The presence of layered plaque at the culprit lesion was associated with high PCATA and low G-CFR in patients with ACS. Detection of layered plaque may indicate increased pericoronary inflammation and impaired coronary flow reserve, potentially providing the risk stratification in patients with ACS. Funding Acknowledgement: Type of funding sources: None.